Family–Related Challenges and Adjustment Strategies of Working-Class Married Women In Kwara State, Nigeria - Ibitoye, O. A; Ajokpaniovo, M; Ajiboye, S. K; Anyanwu, F (International Journal of Educational Management, 2025)
Nigeria is a country where patriarchy is strong. Many men do not support the idea of their wives working while they also work. The men hardly offer full support and co–operation to their wives who are working. These thus give rise to challenges in the home. This study deemed it fit to examine family-related challenges and adjustment strategies of working-class married women in Kwara State, Nigeria. The research design that was adopted for this study is the descriptive survey method. Multi-stage sampling technique was used to select 400 respondents. The instrument used for collecting data is a questionnaire titled “Family Related Challenges and Adjustment Strategies Questionnaire” (FRCASQ). Two research questions and four null hypotheses were generated and tested using t-test and Analysis of Variance (ANOVA). All hypotheses were tested at 0.05 alpha level of significant. The findings revealed that working-class married women are faced with family related challenges such as lack of quality time with my husband; threat from my husband to marry another wife; and frequent quarrel with my husband. The adjustment strategies to family related challenges among married working-class women include: having a mind-set that things will always work out; setting priorities and doing the most important things first; and making use of technology to carry out some house chores like cooking, washing, cleaning etc. Based on the findings of this study, it was recommended that working class married woman should take up jobs that will not be too demanding in order for them to be able to cater for the house hold needs as well as their husbands' needs. By so doing, there will be a peaceful coexistence in the home. Counsellors should organize lectures, seminars, workshop and other participatory programme for working-class married women which would enlighten them on the concept of family related challenges as well as some adjustment strategies for married adults.